Béléko - Gondwe, Jacqueline, 1959- (Luviri Press, 2018)
Béléko is a small village in the West African state of Mali. In the book's twenty-five chapters we meet Dutch development workers, French missionaries and Malian public service workers, health workers, farmers, village women and their children. All of these characters strive in their different ways to give meaning to their lives as their paths cross in the daily village life of Africa at the end of the 1980s. As each character tells his or her own story, we learn of their backgrounds, their passions and their struggles and how they influence each other in decisive ways.